2007
DOI: 10.1007/s11243-006-0180-4
|View full text |Cite
|
Sign up to set email alerts
|

Europium complex of a tridentate ligand: synthesis and spectroscopic properties

Abstract: A new europium complex containing the chelate tridentate ligand and imidazole terpyridine (itpy), was synthesized. The complex was characterized by elemental analysis, mass, FT-IR and photoluminescence spectroscopic techniques. The europium complex in solution showed characteristic luminescence properties. The room temperature photoluminescence spectrum of this complex was composed of typical Eu 3+ red emission assigned to 5 D 0 fi 7 F 2 transition. The metal-centered red emission seemed to be promoted by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The absorption bands assigned to the coordinated Eu-O and Eu-N bonds were observed at 422 cm À1 and 517 cm À1 , respectively. [61][62][63][64][65][66] All these pieces of evidence indicated that the Eu 3+ ions are coordinated to the ligand via the nitrogen atoms of terpyridine and the carbonyl oxygen atoms of the b-diketones.…”
Section: Structural Characterizationmentioning
confidence: 99%
“…The absorption bands assigned to the coordinated Eu-O and Eu-N bonds were observed at 422 cm À1 and 517 cm À1 , respectively. [61][62][63][64][65][66] All these pieces of evidence indicated that the Eu 3+ ions are coordinated to the ligand via the nitrogen atoms of terpyridine and the carbonyl oxygen atoms of the b-diketones.…”
Section: Structural Characterizationmentioning
confidence: 99%
“…Selected IR data (KBr, cm −1 ); 3427(s), 3055(w), 2927(w), 2850(w), 1605(s), 1534(m), 1461(s), 1385(m), 1307(w), 1220(w), 1180(w), 828(w), 742(m). λmax (nm) (ɛ(M − 1 cm −1 )): 241 (78,111), 273 (31,374.5), 324 (13,982) and 411 (20,447)…”
Section: Hydrav-dymentioning
confidence: 99%
“…Lanthanide(III) ions are the best ions with the largest size that are able to form stable complexes with high coordination numbers [11]. In between, lanthanide (III) complexes containing Schiff base provide a highly organized class of compounds with interesting properties such as antifungal [12], antibacterial [13], anticancer [14], catalytic [15], electroluminescence and fluorescence, sensing [16][17][18] biological activities [19], and unique magnetic properties [20].…”
Section: Introductionmentioning
confidence: 99%